Aquatic Toxicology and Hazard Evaluation 1977
DOI: 10.1520/stp32402s
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Fenitrothion Toxicity in Four Life Stages of Rainbow Trout, Salmo gairdneri

Abstract: Lethal and sublethal effects of fenitrothion, an organophosphate insecticide, were investigated in rainbow trout (Salmo gairdneri) embryos, sac fry, fingerlings, and adults. Embryos first exhibited cholinesterase activity 14 days before hatch. Embryos and sac fry at various ages subjected to 34 mg/litre fenitrothion for 24 h under static exposure conditions first exhibited mortality 6 days after hatch. A 24-h lethal concentration of 50 percent of organisms (LC50) of 3.4 mg/litre and a 96-h LC50 of 2.0 mg/litre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In fish, lethal aqueous exposures to AChE inhibitors do not consistently increase fc, which suggests that some other mechanism is responsible for coughing [38]. In fish, lethal aqueous exposures to AChE inhibitors do not consistently increase fc, which suggests that some other mechanism is responsible for coughing [38].…”
Section: Physiological Responsesmentioning
confidence: 93%
“…In fish, lethal aqueous exposures to AChE inhibitors do not consistently increase fc, which suggests that some other mechanism is responsible for coughing [38]. In fish, lethal aqueous exposures to AChE inhibitors do not consistently increase fc, which suggests that some other mechanism is responsible for coughing [38].…”
Section: Physiological Responsesmentioning
confidence: 93%
“…Acetylcholine is a neurotransmitter and is thus essential for normal neural functioning of sensory, integrative and muscular systems. In fish, inhibition of the enzyme affects, for example, respiration, feeding and swimming (Wildish & Lister 1973;Post & Leisure, 1974;Klaverkamp et al, 1977).…”
Section: Nervous Tissuementioning
confidence: 99%
“…Increased fc in chlorpyrifos-intoxicated trout was probably due to an effect unrelated to the primary mechanism of AChE inhibition. In fish, lethal aqueous exposures to AChE inhibitors do not consistently increase fc, which suggests that some other mechanism is responsible for coughing [38]. Klaverkamp et al [38] reported that fenitrothion (0,O-dimethyl 0-(4-nitro-m-tolyl) phosphorothioate) increased coughing in rainbow trout, whereas acephate (0, S-dimethyl acetylphosphoramidothioate) did not.…”
Section: Physiological Responsesmentioning
confidence: 99%